1993
DOI: 10.1002/jts.2490060409
|View full text |Cite
|
Sign up to set email alerts
|

Violence, trauma, and post‐traumatic stress disorder among women drug users

Abstract: INTRODUCTIONNumerous studies have established that exposure to violent traumatic events is associated with a variety of psychiatric disorders, the most obvious of which is post-traumatic stress disorder (PTSD). Persons who have been sexually abused (Briere and Zaidi, 1989) Women who abuse drugs are among those who are likely to be victims of violence (Ladwig and Andersen, 1992). In a study examining violence during pregnancy, women who were victims of a violent attack were more likely than nonvictims to be alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(35 citation statements)
references
References 29 publications
2
26
0
5
Order By: Relevance
“…Asking participants to describe their traumatic experience through the use of leading questions or "probes" may increase the likelihood that they report experiencing a trauma that they did not experience, leading to an overestimate of the prevalence of traumatic experiences. In fact, the use of probes has been shown to increase the frequency of reporting of sexual abuse (Fullilove et al, 1993). This issue appears particularly important given emerging concerns about the possibility ofa "thlse memory syndrome."…”
Section: Operational Definitions and Assessment Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asking participants to describe their traumatic experience through the use of leading questions or "probes" may increase the likelihood that they report experiencing a trauma that they did not experience, leading to an overestimate of the prevalence of traumatic experiences. In fact, the use of probes has been shown to increase the frequency of reporting of sexual abuse (Fullilove et al, 1993). This issue appears particularly important given emerging concerns about the possibility ofa "thlse memory syndrome."…”
Section: Operational Definitions and Assessment Issuesmentioning
confidence: 99%
“…Second is the possibility that participants may underreport their actual levels of exposure to certain traumatic events because of feelings of shame, fear, or discomfort with the subject matter, lack of trust in the interviewer, reticence to share personal information with a stranger (Fullilove et al, 1993 ), or all of the above. Researchers hav e argued that this reporting bias is characteristic of individuals exposed to abuse (e.g., Briere & Zaidi, 1989), but it might also be characteristic of individuals exposed to other forms of trauma.…”
Section: Operational Definitions and Assessment Issuesmentioning
confidence: 99%
“…Researchers have shown that women with PTSD comprise 33% to 59% of substance-abusing females and that symptoms are more severe for these women than for women who experience only one disorder. This percentage is twice as high for women as for men, whose range is from 12% to 34% (Brown et al, 1995;Dansky, Saladin, Brady, Kilpatric, & Resnick, 1995;Fullilove et al, 1993;Ouimette, Brown, & Najavits, 1998).…”
Section: Ptsd and Substance Abuse Prevalencementioning
confidence: 99%
“…For example, alcohol has been shown to compensate for a deficiency in endorphin levels in the brain caused by the traumatic event; thus, a victim may drink in an attempt to control subsequent emotional pain (Volpicelli, Balaraman, Hahn, Wallace, & Bux, 1999). Researchers have suggested that social-contextual factors (e.g., the interpersonal trauma of childhood sexual abuse, domestic violence, and abusive relationships resulting in PTSD) contribute to women's substance abuse at a rate of 32% to 66% (Browne et al, 1999;Dansky, Bume, & Brady, 1999;Fullilove et al, 1993;Volpicelli et al, 1999).…”
Section: The Linkmentioning
confidence: 99%
See 1 more Smart Citation